Pemanfaatan Citra Landsat 8 Oli dan SIG dalam Pemetaan Daerah Rawan Longsor di Kecamatan Way Tenong Kabupaten Lampung Barat - Amin, Muhammad; Ridwan, Ridwan; Asmara, Sandi; Meilani, Kezia Yesi (Jurnal Agricultural Biosystem Engineering, 2023)
Way Tenong Subdistrict is located in West Lampung Regency with an area of ± 11,700 Ha, with relatively unstable soil types and wavy and hilly terrain, making Way Tenong Subdistrict risk to threats from soil activity such as landslides. In 2022 there was a landslide in Way Tenong District which caused damage and fatalities. Because of this situation, some experiment is needed to determine the points that have the potential to experience landslides and the factors that are most dominant in the occurrence of landslides in Way Tenong District, called mapping by utilizing the Geographic Information System (GIS) and Landsat Imagery. The method used in this study is the overlay method (Union) with six parameters, namely slope, soil type. In this study the scores for each class of parameters were added up using a field calculator on the attribute, so that landslide intervals were produced which were divided into five landslide hazard classes, namely not prone, low vulnerability, moderate vulnerability, prone and very vulnerable. From the results of the study it was found that Way Tenong District only had four levels of landslide vulnerability, namely low vulnerability of 176 Ha or 1.50%, medium vulnerability of 5,537 Ha or 47.10%, vulnerability of 4,448 Ha or 37.83% and very vulnerable area of 1,596 Ha or 13.57%, and it can be seen that the dominant factor in the occurrence of landslides in Way Tenong District, West Lampung Regency, is the type of soil. Keywords:  Mapping, Geographic Information System (GIS), Landsat Imagery, Overlay